Maternal Outcome among the Misoprostol Induced Term Pregnant Women - Nahar, Aftabun; Ghani, Afroza; Munira, Serajoom; Khatun, Ashia; Sultana, Rifat; Akter, Fatema Mahbooba (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Use of misoprostol in term pregnancy can give some maternal adverse events. Objective: The purpose of the present study was to see the maternal outcome among the term pregnant women. Methodology: This descriptive, prospective cohort study was carried out in the Department of Obstetrics and Gynaecology at Sir Salimullah Medical College and Mitford Hospital during the period from September 2005 to February 2006. Primi or second gravida patients with the gestational age between 37 weeks to 42 weeks in singleton pregnancy with cephalic presentation and not in labour who came for delivery purposes during the study period at any age were selected as study population. After proper selection of the cases, induction of labour (IOL) was done by applying tablet Misoprostol 5omcg in the posterior vaginal fomix. Purpose of induction of labour was successful when vaginal delivery occurred Without any untoward side effects and Without any surgical interference. Result: A total number of 60 pregnant women were recruited in this study of which 60% patients were within 23-30 years of age. Out of 43 cases of vaginal delivery 22 cases needed 1 dose of Misoprostol 21 cases needed more than 1 dose. 60% of study population who were primigravide had vaginal delivery in 67% cases and caesarean section in 33% cases and among 40% 2nd gravida cases vaginal delivery was 79% and caesarean delivery was 21%. Conclusion: In the conclusion, the use of Misoprostol results in a shorter induction to delivery time, a reduction in the rate of caesarean delivery and also did not appear to produce miserable adverse effects on the method of delivery or the foetus. J Shaheed Suhrawardy Med Coll, 2015; 7(1):6-9